2004
DOI: 10.1124/dmd.32.8.828
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Pomelo on the Metabolism of Tacrolimus and the Activities of Cyp3a4 and P-Glycoprotein

Abstract: ABSTRACT:We recently reported a case of increase in the blood level of tacrolimus following intake of pomelo in a renal transplant recipient. To clarify the mechanism of this increase in the blood level of tacrolimus, we investigated the effect of pomelo juice extract on the activities of CYP3A4 and P-glycoprotein, in comparison with that of extract of grapefruit juice (GFJ). The 10% ethyl acetate extracts of the juice of three pomelos of different origins (Banpeiyu, pomelo I; Hirado Buntan, pomelo II; and Tos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…It was reported that FK506 competitively inhibited CYP3A in human liver microsomes, showing inhibition constants (Ki) of 0.61 mM (Amundsen et al, 2012). Third, the reported concentration of FK506 used in a liver-microsome-based metabolism study of FK506 was 3 ng/ml (Egashira et al, 2004). Thus, to mimic the clinical herb-drug interaction between WZ and FK506, 5 ng/ml of FK506 was chosen in the metabolism study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that FK506 competitively inhibited CYP3A in human liver microsomes, showing inhibition constants (Ki) of 0.61 mM (Amundsen et al, 2012). Third, the reported concentration of FK506 used in a liver-microsome-based metabolism study of FK506 was 3 ng/ml (Egashira et al, 2004). Thus, to mimic the clinical herb-drug interaction between WZ and FK506, 5 ng/ml of FK506 was chosen in the metabolism study.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the recommended oral dose of FK506 is 0.15-0.3 mg/kg twice a day for renal transplant patients. Thus, for a 70-kg subject, taking the volume of the gastrointestinal tract (3-5 l) into consideration (Egashira et al, 2004), the concentration of FK506 in the intestinal surface would be 1-3.5 mg/ml. In addition, a previous study (Pawarode et al, 2007) showed that 1 mM (about 0.8 mg/ml) of FK506 could enhance cellular drug uptake in cells overexpressing P-gp, multidrug resistance-associated protein 1 (MRP-1), or Breast cancer resistance-related protein (BCRP).…”
Section: Discussionmentioning
confidence: 99%
“…આ.Influence of CrJ on the metabolism of PHT by human liver microsomes Human liver microsome assay was performed according to the previous report with a minor modification 9) . In brief, 280 mL of reaction mixture was pre-incubated for 10 min at 37℃ by addition of human / liver microsomes(final concentration;0.48 mg/mL) to the NADPH-regenerating system(1.3 mM NADP, / 3.3 mM glucose 6-phosphate, 0.4 U/mL glucose-6-phosphate dehydrogenase, 3.3 mM MgCl2)in 50 mM phosphate buffer(pH7.4)with 10 mL of CrJ extract (final extract concentration;0.3 and 1%)or SFZ solution(final concentration;0.3 and 1.0 mM).…”
Section: .Extraction Of Beverage With Ethyl Acetatementioning
confidence: 99%
“…Preparation of the cranberry juice(CrJ)extract was performed according to the method reported previously 9) . CrJ was mixed with 3-fold volumes of ethyl acetate and shaken vigorously for 20 min, and the mixture was centrifuged at 900 g for 10 min.…”
Section: .Extraction Of Beverage With Ethyl Acetatementioning
confidence: 99%
“…The mechanism of this interaction involves reversible or irreversible (mechanism-based) inhibition of CYP3A4 in the small intestine (Bailey et al, 2000). In addition, recent reports have indicated that various types of fruits, including those of the citrus species, have an inhibitory effect on CYP3A activities in the liver and gut wall and thereby alter the pharmacokinetics of certain drugs (Di Marco et al, 2002;Bailey et al, 2003;Egashira et al, 2004;von Moltke et al, 2004).…”
mentioning
confidence: 99%